2017
DOI: 10.1080/07347332.2017.1289291
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic growth, distress and attachment style among women with breast cancer

Abstract: Post-traumatic growth, distress and attachment style among women with breast cancer / Romeo, Annunziata; Ghiggia, Ada; Tesio, Valentina; Di Tella, Marialaura; Torta, Riccardo; Castelli, Lorys. -In: JOURNAL OF PSYCHOSOCIAL ONCOLOGY. -ISSN 0734-7332. -35:3(2017), pp. 309-322. Original Citation:Post-traumatic growth, distress and attachment style among women with breast cancer AbstractWe investigated the level of Post-traumatic growth (PTG) and its relationship with clinical and psychological variables in a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…In this regard, it could be interesting to compare in future studies the specificity of this experience to other surgeries or chronic illnesses in order to verify the existence of a disease-related experience of growth. Comparing the total mean PTG scores, liver transplant patients reported PTG levels (2.7) similar to those of breast cancer survivors (with means ranging from 2.3-2.9), 20,21 whereas the total mean score of the present sample was slightly lower than that of survivors who underwent hematopoietic stem cell transplantation (with a mean of 3.0). 20 Moreover, the results of the t test seem to show that the perception of progressing and improving are stable, indicating that a given change is related to the fundamental dimensions of an individual.…”
Section: Discussionmentioning
confidence: 41%
“…In this regard, it could be interesting to compare in future studies the specificity of this experience to other surgeries or chronic illnesses in order to verify the existence of a disease-related experience of growth. Comparing the total mean PTG scores, liver transplant patients reported PTG levels (2.7) similar to those of breast cancer survivors (with means ranging from 2.3-2.9), 20,21 whereas the total mean score of the present sample was slightly lower than that of survivors who underwent hematopoietic stem cell transplantation (with a mean of 3.0). 20 Moreover, the results of the t test seem to show that the perception of progressing and improving are stable, indicating that a given change is related to the fundamental dimensions of an individual.…”
Section: Discussionmentioning
confidence: 41%
“…It seems that active coping mechanisms, such as planning, positive reframing, acceptance techniques and social support are positive strategies that may have the potential to support posttraumatic growth in cancer patients and reduce unmet needs (Schmidt et al, 2002(Schmidt et al, , 2012Romeo et al, 2017Romeo et al, , 2019. According to our findings, we assumed that patients with attachment anxiety suffer from higher unmet supportive care needs due to maladaptive coping strategies.…”
Section: Discussionmentioning
confidence: 73%
“…Fraley et al (2006) found that insecure individuals reported higher levels of distress than secure ones, after the September 11 attack on the World Trade Center. Attachment styles have also been found to be associated to PTG, although limited studies have been carried on in this area and their findings are controversial (Schmidt et al, 2012; Tanyi et al, 2015; Romeo et al, 2017). Concerning breast cancer (BC) patients, the study of Romeo et al (2017) found no significant difference in PTG between women with or without insecure attachment, while Tanyi et al (2015) found that insecure attachment predicted fewer scores on PTG.…”
Section: Introductionmentioning
confidence: 99%